Practical Use and Contemporary Meaning of Post-Industrial Facilities in Poland Based on the Example of Loft Hotels Industry - Sala, Krzysztof (Studies of the Industrial Geography Commission of the Polish Geographical Society, 2020)
The paper addresses the important topic of contemporary trend for revitalising and transforming old industrial buildings into modern commercial facilities. Among many development options, hotel facilities occupy an important place. The opening of modern loft hotels contributes to diversifying the tourist offer, reviving former industrial districts and attracting new tourists into those areas. The aim of the publication is to show that loft facilities, in particular hotels, can contribute to the revitalisation of significant urban areas, improvement of the economic situation and development of entrepreneurship. Research methods used in the work are literary criticism and analysis of the latest secondary data. The publication also uses loose phone calls made in 2019 to managers of well-known loft hotels all over Poland. The publication was written using compact data, scientific articles and netographic data. The results of scientific analysis indicate that loft hotel industry in Poland is developing systematically and is becoming a permanent element of the modern hotel market. The theoretical and practical implications of the work indicate that the beneficiaries of the development of this branch of hospitality will be both cities - hotel headquarters, as well as their clients. Further development of this hotel segment can be expected in the future.